Meatproteome of 2, 4-D degradation analysis between agro chemical contaminated soils - Dakshinamoorthy, Karthika; Solomon Ebenezer, King; Velu, Rajesh Kannan (International Journal of Biological Research, 2013)
Bioremediation is a process to remove pollutants from soil by employing microorganism. One of the most major herbicide that contaminates soil is 2, 4-Dichlorophenoxyacetic acid. There are several molecular and proteomics analyses have been used to find out the biological interaction, but metaproteomics is an ideal tool to study the biological interactions between soil and microorganisms in the ecosystem. The present study has focused on to identify the removal of 2, 4-D by soil microbes. The 2, 4-D degrading bacteria from these soil samples were produced chlorocatechol dioxygenases. Here, 2, 4-D enriched soil samples were studied through experimentally with HPLC and metaproteome of soil were analyzed using SDS-PAGE. Based on the study it has revealed that sample 1 and 3 completely degraded but sample 2 was degraded only 80% on significantly. The preliminary reports of the soil bioremediation study have been provided a paradigm for metaproteomic research on soil biology.